Psychometric Properties of the Sexual Compulsivity Scale in Men Who Have Sex with Men in Spanish Population. - Ibáñez-Tomás, Eduardo; Ballester-Arnal, Rafael; Elipe-Miravet, Marcel; Gasch-Gallén, Àngel (AIDS & Behavior, 2023)
The Sexual Compulsivity Scale (SCS) has been translated, adapted and validated in general Spanish population, making its application difficult in certain groups, such as men who have sex with men (MSM). This paper evaluates the psychometric properties of the SCS in a sample of MSM in Spain. The SCS was administered to 881 participants. The factorial structure of the SCS was examined with an exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Both EFA and CFA confirmed a two-factor structure: (1) Interference of sexual behavior, and (2) Failure to control sexual impulses. Internal consistency was really good for the scale and also for both factors. The SCS also presented adequate psychometric properties. Thus, it is an appropriate measure for assessing sexual compulsivity in MSM, and a tool to be taken into account in future researches to reduce sexual risk behaviors in the MSM Spanish population.